Lecturers’ Talk In Bussiness English Classroom At The Third Semester Of English Education Program Unpari Lubuklinggau - Sastika Seli; Pitri Deliya Sari; Nuril Latifah; Anita Olivia; Sefi Enjelia Winda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT The purpose of this research was to explain the lecturers’ talks in classroom interaction of business English learning. This is a qualitative descriptive research that applied observation and interviews in collecting the data. The data source was the lecturers’ talks when teaching business English courses in the classrooms. The instrument used in this research were observation using video recording and field note as well as the interview list where the researcher record the answers from the questions the researcher asked to the lecturer. And the results of the research from the researcher's analysis show that there are several categories of lecturers' conversations carried out by the lecturers during the classroom interaction. The lecturers’ talks were categorized based on the FIAC System, and they were: accepting feelings, accepting and using students' ideas, asking, and giving directions. The most frequent category of lecturers’ talk were asking questions, and giving directions. Keyword: Lecturer's Talk, Interaction, Classroom Interaction, Business English Class